Biodegradation and potential effect of ranitidine during aerobic composting of human feces. (June 2022) - Zhu, Ping; Pan, Xusheng; Shen, Yilin; Huang, Xiang; Yu, Fang; Wu, Deli; Feng, Qingge; Zhou, John; Li, Xiaowei
Abstract: Ranitidine is widely concerned due to it is mainly related to the transformation into highly toxic carcinogenic products and non-readily biodegradable characteristics in aquatic environment. In this study, biodegradation of ranitidine during rural human feces (HF) aerobic composting was investigated. Results show that both levels of ranitidine are quickly removed in the first-3-day composting. The microorganisms play a vital role in the ranitidine degradation, especially for Firmicutes at the thermophilic period. The effect of ranitidine on the aerobic composting was further analyzed under the normal content (10 mg/kg) and high content (100 mg/kg). The 10 mg/kg ranitidine quickens temperature rise and organic matter degradation of the composting, while the 100 mg/kg ranitidine produces inhibiting effects. However, the effects only occur in the early stage of composting, and then tend to disappear with the removal of ranitidine. Fluorescence spectra confirm that humification and aromatization of dissolved organic matters (DOMs) in the substrates are fastened in 10 mg/kg group, while delayed in 100 mg/kg group. Metagenomic analysis reveals that relative abundances of Firmicutes and sequences related to carbohydrates metabolism increase in the groups mixed with the ranitidine at the early period. The findings provide the first new and systematical insights into degradation characteristics and potential effect of ranitidine during the rural HF composting. Graphical abstract: Image 1 Highlights: Biotransformation of ranitidine was firstly investigated during the composting. Fast biodegradation of ranitidine is found in the HF composting. 10-mg/kg ranitidine improves OM degradation, but 100-mg/kg inhibit the process. The improvement is due to an enhancement of Firmicutes and carbohydrate metabolism. The effect of ranitidine on the composting are mainly found at the early period.